The Springer Index of Viruses - Tidona, Christian; Darai, Gholamreza; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
The continuous growth of knowledege makes it very difficult for scientists to retrieve comprehensive and accurate data on viruses. The desired information is often dispersed in a variety of books, journals and online resources. This encyclopedia presents the latest facts about all known virus in a standardized form created by hundreds of the world's leading virologists. Virus taxonomy represents the basic framework that allows an understanding of the complex evolutionary process that continuously takes place among viruses and their hosts. Each of the 300 taxonomically ordered chapters includes detailed information on individual genus members, historical events, the hosts they can affect (animal, man or plant), virion morphology, genome properties, replication strategy, properties of individual transcripts and proteins, sequence accession numbers, biological properties, diseases, recombinant vector constructs, vaccine strains, key references, as well as a high-resolution particle image and a drawing of the genome organization. Its high content of easily accessible detail information makes this Encyclopedia an indispensable tool for both researchers and lecturers. The new edition includes the recent discoveries made in this field as well as new viruses which have been discovered.
Keywords: Medicine; Microbiology; Medical virology; Biomedicine; Virology; Medical Microbiology; Microbiology